Cardiovascular prevention beyond traditional risk factors: the perinatal programming - Daniele Cocco; Claudio Barbanti; Pier Paolo Bassareo; Giuseppe Mercuro (Hygeia Press di Corridori Marinella, 2018)
It has been long time since "traditional" risk factors for cardiovascular diseases (familial history, smoking habit, diabetes, dyslipidemia, arterial hypertension, ageing, and gender) have been recognized. They are used to provide risk charts to predict the onset of a fatal or non-fatal cardiovascular event (myocardial infarction or stroke) in the next ten years. However, this approach does not explain why a minority of subjects who are not affected by the above mentioned risk factors suffer from heart attack or stroke. Hence, in order to explain these exceptions, researchers have made their efforts to identify other new and previously unmentioned predisposing causes. Prematurity at birth and intrauterine growth restriction, expressed as low birth weight, have been recognized as belonging to these. The aims of this review are to explain the reasons of this recently reported association as well as cite the most recent scientific evidences supporting this theory.